The Antioxidant Effect of Ajwa Dates (Phoenix dactylifera L.) to Inhibit the Progression of Preeclampsia Threats on Pregnant Women through Malondialdehyde as Prooxidant Serum Marker - Ida Royani; Andi Mappaware, Nasrudin; Nur Rezki, Nur Rezki; As’ad, Suryani (Window of Health : Jurnal Kesehatan, 2024)
Hypertension in pregnancy, including preeclampsia, is still a significant problem worldwide and is one of the top three causes of maternal death in Indonesia. The pathophysiology of the disease is unclear yet, but vascular dysfunction due to oxidative stress is thought to play a role. Ajwa dates are known for their antioxidant effects due to their higher phenolic and flavonoids than other dates. The study aimed to determine the impact of consuming seven Ajwa dates each day on the progression of preeclampsia as assessed by changes in malondialdehyde (MDA) levels. Forty pregnant women with gestational age more than 20 weeks were randomly assigned into two groups: the samples of the control group were 10, who were encouraged to consume lots of fruits and vegetables, and the samples of the intervention group were 30, who consumed seven pieces of Ajwa dates every day for eight weeks. MDA measurements were carried out pre-and post-intervention. The intervention group showed a significant reduction in MDA levels following the 8-week intervention period. Consumption of seven Ajwa dates every day can reduce MDA levels significantly and, thus, has the potential to inhibit the progression of preeclampsia in pregnant women who are at risk of preeclampsia based on stress oxidative mechanism.